The Influence of Characteristics and Behavior on the Incidence of Pulmonary Tuberclosis in Al-Hidayah Pesantren, Kejuruan Muda Subdistric Tamiang District, Aceh Province, 2019 - Anggraini, Indah; Hutabarat, Basaria (UI Scholars Hub, 2021)
Introduction. Pulmonary tuberculosis is a chronic infectious disease that is a global issue. Some factors influence the occurrence of pulmonary tuberculosis, among others, the source of infection, a high amount of virulence bacilli, and decreased endurance. This study aims to determine the effect of characteristics and behavior on the incidence of pulmonary TB disease in Al-Hidayah Islamic Boarding School, Vocational School, Aceh Tamiang Regency. Method. This research is analytic with a cross-sectional research design. Data analysis uses Chi-Square test and Logistic Regression) to determine the influence of the most dominant risk factors with pulmonary TB disease incidence. Results. The results showed that the incidence of pulmonary TB had a significant relationship with the variables of age (p=0.002) gender (p=0.031), education (p=0.021), length of stay (p=0.018), knowledge (p=0.020), attitude (p=0.018), and action (p=0.016). Action variable (p=0.025) is the most dominant variable on the incidence of pulmonary TB disease. Conclusion. In order to prevent the occurrence of pulmonary tuberculosis, an increase in outreach activities is carried out. Counseling or IEC to Islamic boarding school students was giving by disseminating information about prevention and prevention of pulmonary TB by using interesting media and easily understood by students such as film screenings so that students can independently live in boarding school and behave healthy life in the prevention of tuberculosis.